Advanced customer analytics : targeting, valuing, segmenting and loyalty techniques - Grigsby, Mike (Marketing science series, 2016)
Providing a clear guide to the specific analytical challenges faced by the retail sector, this no-nonsense book covers the nature and scale of data obtained in transactions, relative proximity to the consumer and the need to monitor customer behavior across multiple channels. --